A Study On The Influence Of Illuminance Quality To Student’s Performance Of Visual Activities: Case Study Of Architecture Studio Room In Universitas Islam Indonesia - Wisnu Hendrawan Bayuaji; Tanty Kesuma Ayu Iswardhani; Alif Angga Risky (Journal of Architectural Research and Design Studies, 2017)
This research aims to measure and evaluate the level of illuminance quality in architecture studio room in relation to the achievement of standard performance and minimum visual comfortableness that should be fulfilled. This study also explores the effect of both illumination quality and quantity to the students physical and psychological performance in conducting visual activities in the architecture studio room. This evaluation will also evaluate the deviation between perception of brightness of users and data measurement by using device related to the achievement of illumination standard of the room. This research is conducted with mix method of quantitative and perceptional with correlational method. The study used empirical data and information from students as the object of research through questionnaire survey and actual data by measurement using luxmeter device to measure the quantity of luminance in the studio room. The data collected indicates that the performance of visual activities that should be achieved require a quite high illuminance quality considering the long duration and continuous activities. This research also explores the importance of determination of visual standard based on the variation of activities compared with the determination of space definition to ensure that all visual activities can be done with optimum performance. The findings indicated that perception of brightness and the adequateness of lighting level in determining visual requirements are two different things in which the adequateness of illuminance level is numerical standard that is determined based on visual observation. The determination of illumination adequacy which is made based on individual perception of brightness may lead to various visual performance standard that may potentially cause illuminance deficiency and as a result may cause various symptoms of eyes fatigues that lead to the decrease of visual performance.Keywords: luminance quality, perception of brightness, continuous visual performance, Architecture studio room